Design and project management robotics education: lessons learned - Ana Lourdes Acuña Zuñiga (Ediciones Universidad de Salamanca, 2012)
The educative projects that include the robotics as resource of education and learning require being plan based on the skills and performances that would consolidate in the population. These skills are the start point to delineate the content emphases, the wished performances, the needed technologies, the processes of training and searching that will be necessary to design. Particularly the educative robotics is propitious to develop or to support productive, creative, digital, communicative abilities.  An indicator, that shows that robotics has become an innovation engine, is observed on the change in the people's attitude and ideas, ways of present and thinking of the students specially, when they become to socialize with others. If those changes are visible now, therefore we are getting close to an innovation because the robotics will have extended its intuitions and it is reflected in its actions and products.